A competency‐based framework for promoting corporate entrepreneurship - Hayton, James C.; Kelley, Donna J. (Human Resource Management, 2006)
AbstractCorporate entrepreneurship, the discovery and pursuit of new opportunities through innovation and venturing, is an important source of competitive advantage. Corporate entrepreneurship involves a diverse set of activities such as innovation in products and processes; the development of internal and external corporate ventures; and the development of new business models, which require an array of roles, behaviors, and individual competencies. In this article, we define individual competencies and distinguish them from other individual difference constructs. We argue that given the unique requirements of corporate entrepreneurship, a competency‐based approach to assessing organizational human capital needs is superior to more traditional job‐analytic methods. Drawing on existing literature, we outline a competency framework for supporting corporate entrepreneurship and infer the underlying, measurable knowledge, skills, and abilities that contribute to these competencies. We conclude with a discussion of the implications of this framework for the staffing, training and development, and performance‐appraisal practices of firms seeking to promote corporate entrepreneurship. © 2006 Wiley Periodicals, Inc.